MOSAiC-ACA and AFLUX - Arctic airborne campaigns characterizing the exit area of MOSAiC - Mech, Mario; Ehrlich, André; Herber, Andreas; Lüpkes, Christof; Wendisch, Manfred; Becker, Sebastian; Boose, Yvonne; Chechin, Dmitry; Crewell, Susanne; Dupuy, Régis; Gourbeyre, Christophe; Hartmann, Jörg; et al. (Scientific Data, 2022)
International audience Two airborne field campaigns focusing on observations of Arctic mixed-phase clouds and boundary layer processes and their role with respect to Arctic amplification have been carried out in spring 2019 and late summer 2020 over the Fram Strait northwest of Svalbard. The latter campaign was closely connected to the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition. Comprehensive datasets of the cloudy Arctic atmosphere have been collected by operating remote sensing instruments, in-situ probes, instruments for the measurement of turbulent fluxes of energy and momentum, and dropsondes on board the AWI research aircraft Polar 5. In total, 24 flights with 111 flight hours have been performed over open ocean, the marginal sea ice zone, and sea ice. The datasets follow documented methods and quality assurance and are suited for studies on Arctic mixed-phase clouds and their transformation processes, for studies with a focus on Arctic boundary layer processes, and for satellite validation applications. All datasets are freely available via the world data center PANGAEA.